From Knowledge to Attitudes: HPV Testing Attitudes and Beliefs Among Students in Health-Related Fields - Sevda Yıldırım; Merve Mert Karadaş (Global Nursing Insights, 2026)
Aim: This study aimed to examine the relationship between HPV and vaccination knowledge and university students’ attitudes and beliefs toward HPV testing.Material and Methods: A descriptive cross-sectional design was employed. Data were collected from 619 undergraduate students enrolled in health-related faculties at a public university through face-to-face surveys. Data were obtained through a socio-demographic information form, the Vaccination and HPV Knowledge Scale, and the HPV Testing Attitudes and Beliefs Scale. Descriptive statistics, independent t-tests, one-way ANOVA, and Pearson correlation analyses were used.Results: Students with higher levels of HPV and vaccination knowledge reported significantly lower personal barriers and social norms scores and higher confidence in HPV testing (p < 0.001). Statistically significant differences in HPV testing attitudes were also observed based on place of residence, academic faculty, paternal education and employment status, and HPV-related education (p < 0.05).Conclusions: The findings indicate that higher levels of HPV and vaccination knowledge are associated with more favorable attitudes and beliefs toward HPV testing among university students enrolled in health-related fields. In addition, students’ attitudes toward HPV testing vary according to sociodemographic and educational characteristics, suggesting that knowledge alone does not fully explain perceptions related to HPV testing.Implication for nursing practice: The findings highlight the importance of integrating sexual and reproductive health education into undergraduate health curricula. Educational efforts should address both informational and psychosocial components to promote more favorable attitudes toward HPV testing among future healthcare professionals.